KONDISI KESEHATAN EKOSISTEM MANGROVE SEBAGAI SUMBER POTENSIAL PENGEMBANGAN EKONOMI KREATIF PESISIR SELAT SUNDA - Adi Susanto; Muta Ali Khalifa; Erik Munandar; Hery Sutrawan Nurdin; Hendrawan Syafrie; Fahresa Nugraheni Supadminingsih; Afifah Nurazizatu Hasanah; Bathara Ayi Meata; Ririn Irnawati; Ani Rahmawati; Achmad Noerkhaerin Putra; Toufik Alansar; Julian Saputra; Bakti Sulistyono; Ahmad Raihan (Leuit (Journal of Local Food Security), 2022)
The functions and benefits of the existence of the mangrove ecosystem are strongly influenced by their health conditions. Ideally, a healthy mangrove ecosystem will provide greater ecological, economic, and service benefits. This study aims to determine the health condition of the mangrove ecosystem as a first step for disaster mitigation and productive economic development in the coastal area of the Sunda Strait. Data collection was carried out in November-December 2021 using the MonMang application in five different villages. The results showed that the highest diversity of mangrove species was found in Cigorondong Village with 9 species including Acanthus ilicifolius, Avicennia marina, Aegiceras corniculatum, Derris trifoliata, Sonneratia caseolaris, Excoecaria agallocha, Lumnitzera racemosa, Ceriops tagal, Heritiera littoralis. The highest canopy cover (79%) was found in the mangrove ecosystem in Citeureup Village and the highest tree density was found in Cigorondong Village at 3,300 individuals/ha. The health condition of the mangrove ecosystem on the coast of the Sunda Strait is moderate because the MHI value obtained is in the range of 33-63%.